Perancangan Aplikasi Kompresi Citra dengan Algoritma Embedded Zero Tree Wavelet - Dwi Suwandi (ADA Research Center, 2025)
The Embedded Zero-Tree Wavelet (EZW) algorithm is a wavelet-based image compression method that offers high-efficiency progressive encoding through the use of a zero-tree structure to represent insignificant wavelet coefficients. This study designs and implements an EZW-based image compression application to address the main problem of image compression, which is finding a balance between a high compression ratio and image reconstruction quality that is still acceptable to the human visual system. The research stages included literature study, algorithm and interface design, program code implementation, and testing using various test images. The results showed that the EZW algorithm was able to achieve a compression ratio of between 87.90% and 93.13%. The compression results showed a significant reduction in file size. For example, an image sized 2311 KB could be compressed to 191 KB, while maintaining good visual quality based on the Peak Signal-to-Noise Ratio (PSNR) and visual evaluation. Compared to conventional methods such as JPEG and Discrete Cosine Transform (DCT), EZW proved to be superior in bandwidth efficiency and artefact reduction in images with high compression rates. This study also identified a research gap in computational efficiency and power consumption when the algorithm is applied to real-time systems, thus requiring further development in hardware optimisation and quantisation stage modification. Thus, this study confirms that EZW-based image compression applications can be an effective solution for digital image storage and transmission needs in environments with limited bandwidth and storage capacity.